Case studies in food policy for developing countries. Volume 2, Domestic policies for markets, production, and environment - Pinstrup-Andersen, Per.; Cheng, Fuzhi (Ithaca, NY : Cornell University Press, 2009)
Volume II of the Case Studies addresses the issues of domestic policies for markets, production, and the environment.
Chapter Eighteen Biodiesel and India's Rural Economy (7-8)Part Three Natural Resource Management Policies; Introduction; Chapter Nineteen Civil Society Strategy to Fight Soil Degradation in Peru (8-1); Chapter Twenty Incentives for Soil Conservation in Peru (8-2); Chapter Twenty-One Environment and Health in Rural Kazakhstan: Linking Agricultural Policy and Natural Resource Management to Rural Welfare (8-3); Chapter Twenty-Two Allocating Irrigation Water in Egypt (8-4).
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Nutrition policy -- Developing countries -- Case studies; Food supply -- Developing countries -- Case studies; Agriculture and state -- Developing countries -- Case studies; Agriculture -- Economic aspects -- Developing countries -- Case studies; BUSINESS & ECONOMICS -- Industries -- General; Agriculture and state; Agriculture -- Economic aspects; Food supply; Nutrition policy; Developing countries; Case studies